Pemberdayaan Pusat Knowledge Sharing Untuk Meningkatkan Keahlian Investigasi Kecurangan Bagi Auditor Internal - Nanda Fatar Julaidi; Agustin Fadjarenie (Jurnal Ekonomi, 2023)
The role of identifying and investigating fraud for organizations and technological developments complicate organizational dynamics and require the competence and expertise of internal auditors to detect fraud within organizations. The purpose of this research is to obtain empirical evidence about the effect of auditors' risk assessment skills, understanding of industry characteristics and knowledge sharing on internal auditors' fraud investigation abilities. The research methodology in this study is quantitative, the population in this study is part of the internal audit of a leading consumer goods company in Indonesia using census techniques with a total of 60 people. Data collection was carried out using a questionnaire. The results of this study, all variables affect the ability of internal audit fraud investigations. This study implies the importance of enhancing the skills of internal auditors by strengthening internal discussions within organizations as “knowledge-sharing centers” to enhance the fraud investigation capabilities of internal auditors.